2021
DOI: 10.1007/s10459-021-10066-7
|View full text |Cite
|
Sign up to set email alerts
|

How does a move towards a coaching approach impact the delivery of written feedback in undergraduate clinical education?

Abstract: Feedback uptake relies on interactions between learners and educators Winstone (Educ Psychol 52: 17–37, 2017). Feedback that coaches using a feedforward approach, is considered to be more personal and emotionally literate Bussey (Bull R Coll Surg Engl 99: 180–182, 2017), Hattie (Rev Educ Res 77: 81–112, 2007). Many modes of feedback are employed in clinical teaching environments, however, written feedback is particularly important, as a component of feedback discourse, as significant time may elapse before a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Roberts et al found that written feedback could be both succinct (on average less than 20 words per comment) and categorized as coaching feedback with recommendations for next steps. 19 As the culture of assessment shifts and CBME becomes engrained in PGME across Canada, we have the opportunity to direct focus on optimizing narrative feedback to train not just competent, but excellent physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roberts et al found that written feedback could be both succinct (on average less than 20 words per comment) and categorized as coaching feedback with recommendations for next steps. 19 As the culture of assessment shifts and CBME becomes engrained in PGME across Canada, we have the opportunity to direct focus on optimizing narrative feedback to train not just competent, but excellent physicians.…”
Section: Discussionmentioning
confidence: 99%
“…3 Feedback that uses coaching language instead of generalized descriptions of the learning interaction is more effective, and signals recommendations for resident improvement. 19 One of the commonly cited barriers to faculty participation in CBME is time; there is an ever-expanding amount of clinical, teaching, and academic duties for a teaching physician. 16,20 With competing interests and depleting resources, making feedback delivery efficient by using words/phrases with the most impact ensures that coaching quality does not suffer under these constraints.…”
Section: Introductionmentioning
confidence: 99%